2021
DOI: 10.1021/acs.energyfuels.1c02134
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influence of Injection–Production Parameters on Challenging Natural Gas Hydrate Exploitation Using Depressurization Combined with Thermal Injection Stimulated by Hydraulic Fracturing

Abstract: The development of low-permeability hydrate reservoirs is facing serious problems. Our previous studies determined that depressurization combined with hot water injection stimulated by hydraulic fracturing (D + Tiw + HF) development mode has an excellent production potential in low-permeability hydrate reservoirs. Based on these, this study further explored the influences of injection–production parameters including injection temperature (T i), injection pressure (P i), and production pressure (P p) on D + Tiw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The initial conditions of the hydrate reservoir are determined according to the process described by Moridis et al , The top and bottom boundaries of the simulated domain (corresponding to the uppermost and lowermost grid block layers, respectively) are set as a constant pressure and temperature. , The geothermal gradient at this site is 0.0443 °C/m with a seabed temperature of 3.7 °C, and the pressure in the sediments is considered to follow a hydrostatic distribution. Then, the temperature and pressure of the boundary layers can be determined, where the pressure is calculated using the pressure, temperature, and salinity-adjusted water density .…”
Section: Methodsmentioning
confidence: 99%
“…The initial conditions of the hydrate reservoir are determined according to the process described by Moridis et al , The top and bottom boundaries of the simulated domain (corresponding to the uppermost and lowermost grid block layers, respectively) are set as a constant pressure and temperature. , The geothermal gradient at this site is 0.0443 °C/m with a seabed temperature of 3.7 °C, and the pressure in the sediments is considered to follow a hydrostatic distribution. Then, the temperature and pressure of the boundary layers can be determined, where the pressure is calculated using the pressure, temperature, and salinity-adjusted water density .…”
Section: Methodsmentioning
confidence: 99%
“…The co-production performances of four development modes were compared, that is, depressurization without stimulation (D), stimulation using fracturing (D+F) or thermal fluid injection (D+T), or both (D+T+F). Additionally, referring to the existing research, the fracture conductivity was set to 10-100 D•cm [21]. Ultimately, the factors examined include stimulation methods, fractured sublayers, fracture spacing, and fracture conductivity, with simulation scenarios presented in Table 2.…”
Section: Simulation Scenariosmentioning
confidence: 99%
“…injecting gases (mainly CO 2 ) that are more likely to form hydrates to replace CH 4 molecules in NGH cages [19]; v. injecting chemical inhibitors like brine to promote NGH dissociation [20]; vi. integrating multiple methods, such as combining fracturing and multi-well systems [21], and using thermal stimulation and chemical inhibitors [22]. Nevertheless, these studies mainly focus on the production dynamics of reservoirs with a single HBL, with few simulations exploring the commingled production of multilayers.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al explored the influence of different heat injection pressures, temperatures, and production pressures on mining using the above scheme. They found that the hydrate dissociation and gas production rates increased linearly with an increase in the heat injection temperature pressure and a decrease in the production pressure before t wb but showed the opposite trend after t wb .…”
Section: Hydraulic Fracturingmentioning
confidence: 99%
“…Furthermore, horizontal fracture conductivity is the main influencing factor for improving gas production, whereas the influence of vertical fracture conductivity is negligible. An optimal fracture spacing exists and the hydrate decomposition performance is significantly improved when the fracture spacing is less than 2 m. Chen et al 105 explored the influence of different heat injection pressures, temperatures, and production pressures on mining using the above scheme. They found that the hydrate dissociation and gas production rates increased linearly with an increase in the heat injection temperature pressure and a decrease in the production pressure before t wb but showed the opposite trend after t wb .…”
Section: Fracture Formation and Developmentmentioning
confidence: 99%